A study of consumers attitude toward counterfeit products at Kota Samarahan Sarawak / Nurjanah Baizura Jeman - Jeman, Nurjanah Baizura (2015)
This project paper titled "A Study of Consumers' Attitude toward Counterfeit Products at Kota Samarahan Sarawak" is undertaken in the Faculty of Business and Management at Universiti Teknologi Mara. 381 respondents have involved in this survey which was conducted for two weeks and the data from the questionnaires were analyzed and computed as mean score. The purpose of this study is to determine factors influencing customer attitudes among Kota Samarahan residents. Based on the types of population background, three factors were tested which are Psychographic, Product Attributes and Price Determinants. From this research, Price Determinants is the most influencing factor of consumer attitudes towards counterfeit products. This research also discovers types of counterfeit products usually purchased by Kota Samarahan residents and the result shows that watch is the most consumers' purchases in online shopping. This research also determines that there is a significant relationship between factors and reliability. Overall, this study provides a greater knowledge sharing for the marketers and manufacturers of genuine branded products. Knowing the attitude plays a role in determining the purchase intention of a consumer, manufacturers and marketers can work on finding ways to change consumers' attitude and beliefs.